Petroleum Source Rock Evaluation in the Eastern Fold Belt, Bengal Basin, Bangladesh: An Integrated Study Using Seismic, Well Log, Field Investigation, and Laboratory Analysis Data (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
This study focuses on the source rock, a critical component of the petroleum system, within the Eastern Fold Belt (EFB) of Bangladesh. It aims to assess the occurrence and quality of source rocks by employing a comprehensive approach that includes fieldwork, laboratory analysis, seismic interpretation, and well data. The research was conducted in the Sylhet and Khagrachari regions, where prior source rock evaluations were inadequate. Organic carbon content evaluation using TOC analysis reveals a substantial presence of source rock in the EFB, which can produce hydrocarbon upon maturation. Depositional environment analysis suggests the source rocks were deposited in geological settings, including the continental shelf, prodeltaic, shallow marine, and deltaic sub-environments. Laboratory studies indicate the total organic carbon (TOC) content varied, ranging from 0.24% to 1.812%, with an average TOC of 0.65% to 0.7% in Sylhet and an average TOC of 0.28% to 0.33% in Khagrachari where the Kopili Shale of Sylhet exhibiting the highest amount of organic content. The samples from the northern part of the Bengal Basin were observed to be richer in organic content than those from the southern regions. Well-log data from Fenchuganj show that the source rocks are located at depths ranging from 3500 to 4200 m, which is correlated by seismic data. This depth suggests that the source rocks have undergone sufficient thermal maturation (in the temperature window of 105 -140℃) to generate hydrocarbons. Seismic sections further demonstrate the regional distribution of source rock, reinforcing the potential for gas-prone hydrocarbon prospects in the EFB. The integrated approach provides valuable insights into the petroleum potential, emphasizing the crucial role of source rocks in the EFB for future hydrocarbon exploration efforts in the Bengal Basin, offering hope for future discoveries.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(2), 2024, P 77-104